Active equalization control strategy of Li‐ion battery based on state of charge estimation of an electrochemical‐thermal coupling model. (3rd February 2020) - Lin, Yuzhen; Xu, Xing; Wang, Feng; Xu, Qiling
Summary: Aiming at solving the problem of poor battery cell consistency caused by excessive decay of cell capacity or increased internal resistance during the operation of lithium‐ion battery packs for vehicles, the paper proposes an active equalization control with 12‐V power supply as an equalization energy source, which achieves efficient energy replenishment of individual cells with low power. The electrochemical‐thermal coupling model of lithium‐ion battery is built, and the order reduction of large‐scale system theory ensures that the model had higher accuracy and lower amount of calculation, which is suitable for vehicle battery management system (BMS). Then the extended Kalman filter algorithm is used to calculate the real‐time state of charge (SOC) of each cell and set as an equalization variable. The equalization simulation circuit is built with MATLAB/Simulink, the experimental platform of active equalization system for battery packs is constructed, and the battery packs are tested for equalization in static state. The simulation and experimental results show that the proposed active equalization control strategy can rapidly improve the voltage inconsistency between single cells, and the energy transfer efficiency can reach about 85% during the equalization process. Abstract : We designed an equalization circuit with the vehicle 12‐V power supply as the external power supply, and the real‐time state of charge (SOC) of the single battery is selected as the equalization variable. The estimation of SOC is based on the electrochemical‐thermal coupling model of the battery. The external energy source equalization principle based on the capacitive circuit is used to build the simulation circuit to verify the performance of the equalization circuit.